Transoesophageal echocardiography in the longitudinal axis: correlation between anatomy and images and its clinical implications. Issue 4 (October 1990) - Stümper, O; Fraser, A G; Ho, S Y; Anderson, R H; Chow, L; Davies, M J; Roelandt, J R; Sutherland, G R
Abstract : Transoesophageal echocardiographic imaging in the longitudinal axis is a recent addition to the non-invasive evaluation of congenital and acquired heart disease. The technique provides unique images of intracardiac anatomy but their interpretation remains difficult. A heart specimen was therefore cut according to the echocardiographic imaging planes to elucidate the morphological details. The results suggested that longitudinal transoesophageal imaging complements the transverse axis approach. It gave new imaging information on the right ventricular outflow tract and the pulmonary trunk, the atrioventricular valves, the interventricular septum, the cardiac apex, and the thoracic aorta. In particular, it showed the entire length of the right ventricular outflow tract. When longitudinal imaging was used in combination with transverse imaging almost all the thoracic aorta could be examined. Imaging in the longitudinal axis may also allow better assessment of the mechanisms of atrioventricular valve regurgitation.